A Comprehensive Analysis of Public Choices in Mass Transport and Assessing Development Challenges in The Transportation Sector - Ipoeng Martha Marsikun; Paulus Israwan Setyoko; Hikmah Nuraini; Muslih Faozanudin; Denok Kurniasih (CV. Publikasi Indonesia, 2024)
The primary objective of this research is to investigate public transportation governance in Banyumas Regency using the New Public Management (NPM) paradigm, with the aim of enhancing efficiency and effectiveness. The study focuses on understanding the factors that influence people's preferences for public transportation modes, particularly in relation to availability, cost, comfort, safety, and environmental concerns. The research also aims to address the challenges associated with the perception of private vehicles as status symbols, recognizing their impact on economic and societal development. The study employs quantitative methods and the SmartPLS4 analysis tool to uncover significant findings regarding the positive impacts of availability and comfort on preferences and the varying influences of cost, environment, and security. The ultimate goal is to provide insights that can inform the development of transportation policies, promoting effectiveness and alignment with the community's needs in Banyumas Regency.